PENGELOLAAN KELAS DAN METODE STUDI LITURGI DALAM RANGKA PEMAHAMAN MATERI SAKRAMEN BAPTIS BAGI SISWA KELAS VIII-A DI SMP SANTO ANTONIUS JAKARTA - Simon Saulinggi; Restituta Nurhaeni (Jurnal Manajemen Pendidikan, 2013)
The purpose of the classroom action research is: 1) to know how far the Liturgical study method which uses enhanced materials may improve class VIII-A students’ academic achievement, especially regarding Baptism; 2) to improve students’ comprehension regarding the material given by the teacher in class; 3) to enhance teachers’ critical minds on finding alternative solutions to solve the problem found in the teaching and learning environment.The formulation of the problem in this classroom action research is how a classroommanagement and Liturgical study method can altogether improve the comprehension of the sacrament of baptism material for the VIII-A’sgrade students of yunior high school of Santo Antonius, Jakarta.The research methodthat is used in thisclassroom action isthe Kemmis’s and McTaggart’s model, that consisted of three cycles,consisted of four steps, which are: 1)Planning; 2) Excecution; 3) Observation; 4) Reflection. Each cycles isheld in two sessionsduring the learning activities.The result of the research shows that through an organized classroom action research and liturgical study method, teachers are able to improve the quality and students’ activities on their learning process, and also to increase students’ ability to understand the learning material given, especially the material about Baptism. On cycle 1, 4 students passed the criteria and 26 others didn’t, with the average score of 74.40. Cycle 2 resulted that 21 students passed and 9 didn’t, with the average score of 87.06. On cycle 3, 29 students passed and 1 didn’t, with the average score of 93.16. This result exceeded the minimum target scoreof competence indicator which has been declared by the school, which is 80 point.To conclude, through a good classroom management and the usage of Liturgical method study on the teaching and learning of Catholic study for class VIII-A in Santo Antonius Junior High School, Rawabunga, Jatinegara, East Jakarta, can be an alternative to be chosen and implemented by teachers of junior high school in order to improve students’ ability in understanding Catholic study materials, especially about Baptism.Keywords :Classroom Management, Liturgical Study Method, Sacrament of Baptism Material